Exhaled Aerosols in SARS-CoV-2 Polymerase Chain Reaction-Positive Children and Age-Matched-Negative Controls - Gutmann, Desiree; Donath, Helena; Herrlich, Laura; Lehmkühler, Timon; Landeis, Anton; Ume, Emily R.; Hutter, Martin; Goßmann, Ann-Kathrin; Weis, Frederik; Weiß, Maximilian; Rabenau, Holger F.; Zielen, Stefan (Frontiers in Pediatrics, 2022)
Background: Children and adolescents seem to be less affected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease in terms of severity, especially until the increasing spread of the omicron variant in December 2021. Anatomical structures and lower number of exhaled aerosols may in part explain this phenomenon. In a cohort of healthy and SARS-CoV-2 infected children, we compared exhaled particle counts to gain further insights about the spreading of SARS-CoV-2. Methods: In this single-center prospective observational trial, a total of 162 children and adolescents (age 6-17 years), of whom 39 were polymerase chain reaction (PCR) -positive for SARS-CoV-2 and 123 PCR-negative, were included. The 39 PCR-positive children were compared to 39 PCR-negative age-matched controls. The data of all PCR-negative children were analyzed to determine baseline exhaled particle counts in children. In addition, medical and clinical history was obtained and spirometry was measured. Results: Baseline exhaled particle counts were low in healthy children. Exhaled particle counts were significantly increased in SARS-CoV-2 PCR-positive children (median 355.0/L; range 81-6955/L), compared to age-matched -negative children (median 157.0/L; range 1-533/L; p<0.001). Conclusion: SARS-CoV-2 PCR-positive children exhaled significant higher levels of aerosols than healthy children. Overall children had low levels of exhaled particle counts, possibly indicating that children are not the major driver of the SARS-CoV-2 pandemic. Trial Registration: Trial was registered under ClinicalTrials.gov Identifier: NCT04739020.